JOACHIM DUY BELLAY, FRENCH LANGUAGE PROMOTER (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In this article there is defined about the essence of French writer Duy Bellay's work “Glorifying and protecting the French language”, that is, the need to create French literature and culture based on humanistic principles, the aesthetic judgement of the French language more than fiction and poetic art.